2009
DOI: 10.1038/nature08398
|View full text |Cite
|
Sign up to set email alerts
|

Role of the polycomb protein EED in the propagation of repressive histone marks

Abstract: Summary Polycomb Group (PcG) proteins play an essential role in the epigenetic maintenance of repressive chromatin states. The gene silencing activity of the Polycomb Repressive Complex 2 (PRC2) depends on its ability to tri-methylate lysine 27 of histone H3 (H3K27) via the catalytic SET domain of the EZH2 subunit, and at least two other subunits of the complex: Suz12 and Eed. We show that the C-terminal domain of Eed specifically binds to histone tails carrying tri-methyl lysine residues associated with repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
1,126
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,063 publications
(1,170 citation statements)
references
References 40 publications
40
1,126
0
4
Order By: Relevance
“…During replication, parental histones re-associate locally with newly synthesized DNA in budding yeast (22). H3K27me3 marks appear to propagate via replication in Drosophila (23). However, whether this mechanism is conserved in vertebrates, is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…During replication, parental histones re-associate locally with newly synthesized DNA in budding yeast (22). H3K27me3 marks appear to propagate via replication in Drosophila (23). However, whether this mechanism is conserved in vertebrates, is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,6 In addition, EED binds to trimethylated H3K27 (H3K27me3) through the so-called 'aromatic cage' composed of three aromatic amino acids (Phe97, Trp364 and Tyr365) to activate PRC2. 1,7 A previous report demonstrated that PRC2 complexes possessing an aromatic-cage mutation in EED show severely reduced enzymatic activities in the presence of H3K27me3 peptides. 7 EED haploinsufficiency (Leu196Pro) in mice leads spontaneously to a myeloproliferative disorder, 8 and exposure of hypomorphic (Ile193Asn) homozygotes to genotoxic stresses gives rise to tumorigenesis.…”
mentioning
confidence: 99%
“…1,7 A previous report demonstrated that PRC2 complexes possessing an aromatic-cage mutation in EED show severely reduced enzymatic activities in the presence of H3K27me3 peptides. 7 EED haploinsufficiency (Leu196Pro) in mice leads spontaneously to a myeloproliferative disorder, 8 and exposure of hypomorphic (Ile193Asn) homozygotes to genotoxic stresses gives rise to tumorigenesis. 8,9 These findings strongly suggest that dysfunction of EED might be involved in the pathogenesis of myeloid disorders.…”
mentioning
confidence: 99%
“…For example, H3K27 trimethylation, is both catalyzed and recognized by the PRC2 methyltransferase complex (Hansen et al, 2008). The PRC2 subunit, EED, binds H3K27me3 both to recruit the PRC2 complex and to allosterically activate its methyltransferase activity, setting up a positive feedback loop to propagate the epigenetic mark through cell division without need for sequence specific factors (Margueron et al, 2009). In this context, many chromatin modifications are not in fact epigenetic.…”
Section: Molecular Mechanism Of Transcriptional Regulation and Epigenmentioning
confidence: 99%